Heme: emergent roles of heme in signal transduction, functional regulation and as catalytic centres - Shimizu, Toru; Lengalova, Alzbeta; Martínek, Václav; Martínková, Markéta (Chemical Society reviews, 2019)
Protoporphyrin IX iron complex (heme) is an important cofactor for oxygen transfer, oxygen storage, oxygen activation, and electron transfer when bound to the heme proteins hemoglobin, myoglobin, cytochrome P450 and cytochrome c, respectively. In addition to these prototypical heme proteins, there are emergent, critical roles of exchangeable/labile heme in signal transduction. Specifically, it has been shown that association/dissociation of heme to/from heme-responsive sensors regulates numerous functions, including transcription, DNA binding, microRNA splicing, translation, protein kinase activity, protein degradation, heme degradation, K+ channel function, two-component signal transduction, and many other functions. In this review, we provide a comprehensive overview of structure-function relationships of heme-responsive sensors and describe new, additional roles of exchangeable/labile heme as functional inhibitors and activators. In order to complete the description of the various roles of heme in heme-bound proteins, we also mention heme as a novel chemical reaction centre for aldoxime dehydratase, cis-trans isomerase, N-N bond formation, hydrazine formation and S-S formation, and other functions. These unprecedented functions of exchangeable/labile heme and heme proteins should be of interest to biological chemists. Insight into underlying molecular mechanisms is essential for understanding the new role of heme in important physiological and pathological processes.
Keywords: Catalytic Domain; molekulární modely; hemoproteiny; signální transdukce; Models, Molecular; Protein Interaction Maps; mapy interakcí proteinů; Heme; hem; Animals; lidé; Hemeproteins; katalytická doména; zvířata; Humans; Signal Transduction